The Use of Cohesive Devices in English Education Journal Articles Written by Graduate Students of UNNES - faza, Faizah; Sutopo, Djoko; Faridi, Abdurrachman (Universitas Negeri Semarang, 2020)
This study was a discourse analysis aimed to investigate the use of cohesive devices in English education journal articles written by graduate students of UNNES. The objectives of this study are to analyze cohesive devices in the article in order to explain the use of references in journal articles written by graduate students of UNNES, to analyze cohesive devices in the article in order to explain the use of substitutions in journal articles written by graduate students of UNNES, to analyze cohesive devices in the article in order to explain the use of ellipses in journal articles written by graduate students of UNNES, to analyze cohesive devices in the article in order to explain the use of conjunctions in journal articles written by graduate students of UNNES, to analyze cohesive devices in the article in order to explain the use of reiterations in journal articles written by graduate students of UNNES, to analyze cohesive devices in the article in order to explain the use of collocations in journal articles written by graduate students of UNNES. The objects of this research were English journal articles which are written by graduate students of UNNES. The 15 English education journal articles were analyzed using Halliday and Hasan’s (1976) theory. The results of this study showed that graduate students of UNNES used 6 types of cohesive devices, namely repetition, substitution, ellipsis, conjunction, reiteration, and collocation. References were more frequently than the other cohesive devices. On the other hand, the undergraduate students of UNNES rarely used substitution and ellipsis to achieve their writing.